The Effect of Audit Delay, Public Ownership and Financial Distress on Auditor Switching - Sofia Febri Isniartuti; Asih Handayani (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
This study investigates the influence of audit delay, public ownership, and financial distress on auditor switching, focusing on property and real estate sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Employing a quantitative research method, the study adopts a descriptive and verification approach. A total of 33 companies were selected through purposive sampling based on specific criteria relevant to the research objectives. Data analysis was conducted using logistic regression with E-Views 12 software to test the proposed hypotheses. The findings reveal that audit delay, public ownership, and financial distress collectively exert a significant effect on auditor switching decisions. However, when examined individually, only audit delay shows a statistically significant impact on auditor switching, while public ownership and financial distress do not demonstrate significant partial effects. These results suggest that timeliness in audit completion plays a critical role in influencing companies’ decisions to change auditors, potentially reflecting concerns over audit quality or regulatory compliance. Meanwhile, ownership structure and financial condition appear to have less influence in isolation. The study highlights the importance of monitoring audit timeliness as a key factor in auditor-client relationships and provides insights for regulators, investors, and corporate governance stakeholders in evaluating audit practices within the property and real estate industry.